2008
DOI: 10.1007/s12011-008-8161-4
|View full text |Cite
|
Sign up to set email alerts
|

Heme Iron Uptake by Caco-2 Cells is a Saturable, Temperature Sensitive and Modulated by Extracellular pH and Potassium

Abstract: It is known that heme iron and inorganic iron are absorbed differently. Heme iron is found in the diet mainly in the form of hemoglobin and myoglobin. The mechanism of iron absorption remains uncertain. This study focused on the heme iron uptake by Caco-2 cells from a hemoglobin digest and its response to different iron concentrations. We studied the intracellular Fe concentration and the effect of time, K+ depletion, and cytosol acidification on apical uptake and transepithelial transport in cells incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…HO-1 activity can be increased 10-to 100fold by various conditions, including hyperthermia, heme, and heavy metals such as cobalt and cadmium (36,37). It was suggested that increased HO-1 activity and expression might be responsible for the increased heme iron absorption and a rapid export of heme iron (38,39). Heme iron transport was increased in cells treated with cadmium (38) and the increased heme iron transport was associated with the increased HO-1 protein by heme (39) in Caco-2 cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 activity can be increased 10-to 100fold by various conditions, including hyperthermia, heme, and heavy metals such as cobalt and cadmium (36,37). It was suggested that increased HO-1 activity and expression might be responsible for the increased heme iron absorption and a rapid export of heme iron (38,39). Heme iron transport was increased in cells treated with cadmium (38) and the increased heme iron transport was associated with the increased HO-1 protein by heme (39) in Caco-2 cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…The (GT) n repeat was located between the putative heat-shock element and the cis-regulatory element [21] and an increased expression of HO-1 gene may not be beneficial for the host, because HO participates actively in the heme degradation, and the iron released in this reaction could be potentially toxicity for the cell. Also, it must be considered that HO protein expression is increased in cells incubated with increased concentration of inorganic iron [24]. Recent studies have revealed that increased oxidative stress in diabetic rats leads to the induction of HO-1 [25], and it was suggested that the 5′-flanking polymorphism in the HO-1 gene is associated with the development of oxidative stress-mediated diseases, where subjects possessing S/S showed higher expressions of HO-1 mRNA and HO activities [22].…”
Section: Discussionmentioning
confidence: 99%
“…Esto se conoce con el nombre de liberación controlada (Figura 1D). 7) La encapsulación también permite la posibilidad de mezclar en una misma micro-partícula/micro-cápsula/ liposoma, dos fuentes diferentes de hierro (Figura 1A), ya que el hierro no hemo se absorbe por el transportador de metales divalentes 1 (DMT1), y el hemo mediante la proteína transportadora del grupo hemo 1 (HCP1), y ambos receptores son saturables 1,21 . También con compuestos que promuevan su absorción.…”
Section: Introductionunclassified